Synthesis, structural and mechanical characterization of sputtered tungsten oxide coatings - Parreira, N. M. G. (2006)
Tungsten oxide coatings were deposited without substrate bias by DC reactive magnetron sputtering of a tungsten target using oxygen as reactive gas. By tuning the partial pressure of oxygen (pO2/pAr) between 0 and 4, the oxygen content of the films was changed from 0 to 75 at.%. The structure of the films (investigated by X-ray diffraction) depends on their oxygen content. For low oxygen contents, the [alpha]-W and [beta]-W3O phases were observed (< 30 at.%), and with the increase of oxygen content (30 at.% < O < 67 at.%) the structure became amorphous. A transition region was obtained for oxygen content between 67 at.% and 75 at.%, and when O > 75 at.%, a nanocrystalline (WO3) structure was reached.